Finite element models of wedge disclination - Takafumi HOSOYA; Hiroyuki KATO; Kazuaki SASAKI (Nihon Kikai Gakkai ronbunshu, 2014)
Numerical analysis of the elastic stress field around a wedge-type disclination is first presented. Disclinations are lattice defects accompanied by multi-valued displacement field. The discontinuity in displacement is dealt with finite element method in two different ways; one is to build up finite element model with rotational discontinuity in its original shape, and the other is to give the initial strain capable of expressing the displacement field. Good agreement with the analytical solution in elasticity was obtained in both of the two methods. It is suggested that the initial strain method may be more appropriate when solving complex structures numerically because it does not need starting with cut-and-joint procedure to create a disclination.